PENGELOLAAN KESIAPAN BELAJAR ANAK MASUK SEKOLAH DASAR - Rifai, Mohamad; Fahmi, Fahmi (Tarbawi, 2017)
Readiness of children to enter school is something that is very important that every child must have because the readiness to attend school is the first capital to follow the process of learning activities in school. The greater the readiness of the child, the greater the child has the ability to follow the poses of learning activities at school. Conversely, the smaller the readiness of children's learning, the smaller the children have the ability to follow the poses of learning activities at school. The problem is that many children do not have readiness to learn well because parents have not manage the readiness to learn children enter school well. In the readiness of learning children enter primary school can not come suddenly in the child because everything must be well prepared, including that of elementary school age, cognitive, affective, and psychomotor ability of children and others needed by children. The role of parents and teachers in "pre-school" institutions / education at an early age is very important in managing preparing children for elementary school. Having the readiness to learn elementary school entrance well then the child can enjoy the process of learning activities and the opportunity / opportunity to deliver to achieve the best achievement in learning. Keywords: Learning Readiness, Maturity Character, Readiness Factors and Parent and Teacher Cooperation